Metformin Reverts Deleterious Effects of Advanced Glycation End-Products (AGEs) on Osteoblastic Cells - Schurman, León (2007)
Advanced glycation endproducts (AGEs) are implicated in the complications of diabetes and ageing, affecting several tissues, including bone. Metformin, an insulin-sensitizer drug, reduces the risk of life-threatening macrovascular complications. We have evaluated the hypothesis that metformin can abrogate AGE-induced deleterious effects in osteoblastic cells in culture. In two osteoblast-like cell lines (UMR106 and MC3T3E1), AGE-modifi ed albumin induced cell death, caspase- 3 activity, altered intracellular oxidative stress and inhibited alkaline phosphatase activity. Metformin-treatment of osteoblastic cells prevented these AGE-induced alterations. We also assessed the expression of AGE receptors as a possible mechanism by which metformin could modulate the action of AGEs. AGEs-treatment of osteoblast-like cells enhanced RAGE protein expression, and this up-regulation was prevented in the presence of metformin. Although the precise mechanisms involved in metformin signaling are still elusive, our data implicate the AGE-RAGE interaction in the modulation of growth and differentiation of osteoblastic cells.